Coral mortality discrimination and habitat phase shift analysis using landsat TM and ETM+ imageries of Balabac, Palawan - Abella, Margaux Angelica R. (2007)
This study aimed to address the problem of discriminating not only among general benthic cover classes but also between coral mortality states using image classification. More importantly patterns in phase shifts of coral reef environments were studied using post-classification change detection and spatial analysis to determine which directions of change were most prevalent in the study areas, at what exact locations they occurred, and what factors may have contributed to the change.